Investigation on Probable Association Between IL-13, IL-13RA1, and IL-13RA2 Genes Polymorphism and Pulmonary Tuberculosis - Li HM; Tang F; Huang Q; Pan HF; Zhang TP (Dove Medical Press, 2022)
Hong-Miao Li,1 Fei Tang,2 Qian Huang,3 Hai-Feng Pan,1 Tian-Ping Zhang4 1Department of Epidemiology and Biostatistics, School of Public Health, Anhui Medical University, Hefei, People's Republic of China; 2Department of Interventional Pulmonology and Endoscopic Diagnosis and Treatment Center, Anhui Chest Hospital, Hefei, People's Republic of China; 3Department of Public Health, Medical Department, Qinghai University, Xining, People's Republic of China; 4The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People's Republic of ChinaCorrespondence: Tian-Ping Zhang, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People's Republic of China, Email zhangtianping@ustc.edu.cn Hai-Feng Pan, Department of Epidemiology and Biostatistics, School of Public Health, Anhui Medical University, Hefei, People's Republic of China, Email panhaifeng1982@sina.comObjective: Our study aimed to explore the association of IL-13, IL-13RA1, and IL-13RA2 genes polymorphisms with PTB susceptibility and its clinical features.Methods: Nine SNPs were genotyped by improved multiple ligase detection reaction (iMLDR) in 476 PTB patients and 473 controls. The association between these SNPs and PTB risk was analyzed using SPSS software and haplotype analysis was assessed using SHEsis software.Results: The IL-13RA1 rs2495636 GA genotype frequency in PTB patients was significantly decreased, and IL-13RA2 rs5946039 A allele was related to the lower risk of PTB. In IL-13 gene, rs20541 variant was found to be associated with PTB risk under recessive mode. Moreover, IL-13RA1 rs141573089 C allele was significantly lower in PTB presenting with fever, drug resistance, and CC genotype was decreased in PTB presenting with leukopenia. IL-13RA1 rs2495636 polymorphism was associated with drug resistance, pulmonary infection, and IL-13RA2 rs3795175, rs638376 polymorphisms were related to drug resistance in PTB patients.Conclusion: IL-13 rs20541, IL-13RA1 rs2495636, IL-13RA2 rs5946039 polymorphisms might be contributed to the genetic background of PTB in Chinese population.Keywords: pulmonary tuberculosis, Mycobacterium tuberculosis, interleukin-13, single nucleotide polymorphisms